AN INTEGRATED GNSS, DATUM TRANSFORMATION, AND IOT FRAMEWORK FOR DIGITAL GEODETIC CONTROL POINT INFRASTRUCTURE IN URBAN ENVIRONMENTS - Oladosu, Stephen Olushola; Nwodo, Geoffrey Ogbonna; Ehigiator-Irughe, Raphael (FUDMA Journal of Sciences, 2026)
Accurate and accessible geodetic control point information is essential for modern surveying, mapping, and geospatial data infrastructure development. However, conventional analogue-based documentation systems are often fragmented, poorly maintained, and inefficient, particularly in rapidly urbanizing environments. This study presents the development and implementation of a semi-automatic Internet of Things (IoT)-enabled virtual repository for the storage, management, and retrieval of geodetic control point data, integrating high-precision Global Navigation Satellite System (GNSS) observations with systematic datum transformation. Static GNSS observations were conducted at selected control points in Benin City, Nigeria, and processed using continuously operating reference station (CORS) corrections to obtain precise three-dimensional coordinates in both the local Minna datum and the global WGS84/ITRF reference frame. Datum transformation was applied to evaluate positional consistency between the two coordinate systems, and the derived datasets were integrated into a centralized IoT-based web platform for real-time data access, visualization, and archival management. The results achieved centimetre-level horizontal accuracy and decimetre-level vertical precision, confirming the robustness of the adopted GNSS methodology. Comparative analysis revealed systematic horizontal shifts of less than 0.5 m and vertical discrepancies approaching 1.0 m, emphasizing the importance of accurate transformation models. The developed platform demonstrated efficient data storage, rapid retrieval, and reliable accessibility, providing a scalable solution for modernizing geodetic infrastructure, supporting smart city initiatives, and strengthening spatial data governance in developing urban environments.